If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = sqrt(2x + 1) + 3 Multiply f * x fx = sqrt(2x + 1) + 3 Reorder the terms: fx = qrst(1 + 2x) + 3 fx = (1 * qrst + 2x * qrst) + 3 fx = (1qrst + 2qrstx) + 3 Reorder the terms: fx = 3 + 1qrst + 2qrstx Solving fx = 3 + 1qrst + 2qrstx Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 3x-1 + qrstx-1 + 2qrst Simplifying f = 3x-1 + qrstx-1 + 2qrst Reorder the terms: f = 2qrst + qrstx-1 + 3x-1
| 4y-12=36 | | 4b-3-10b-8= | | L+N=62 | | 6a-10=2a | | x^2+4y^2-6x-24y+39=0 | | 0=4cos(4x)-2 | | 7.5+0.5x=13 | | X+(x+4)+(x+8)=445 | | 4+8x=4(1+2x) | | 2x+7=27X | | A=2(6)+2(7)+5 | | A=2(6)LH+2(7)WH+5LH | | 2.7x+4.5y=5022 | | A=2(5)+2(4)+10 | | -4(y+7)=-6y-44 | | 3x-(3x-4)=4 | | 12x=32-2x | | x-a+2=ax-3x+5a | | A=5L+4W+10w | | 3a-4=-5a+2 | | 3x^2+12x+17=12 | | 3a-4=-5a+2a+2 | | (A)(.5)(3.5)=7000 | | -3(x-5)=-7x-25 | | 40x^2+9x-106=0 | | 4(u-7)-3=-4(-4u+7)-6u | | 3(3n+-4)+8(7+2n)= | | 40x^2+9x+106=0 | | 40x^2+9x+32=0 | | 2(x+7)+2=4+3x | | -16=8(v+4)+8v | | 4x^2+30x-44=0 |